Analisis Penerapan Prinsip Penyajian Dan Pengungkapan (PPP) Standar Akuntansi Keuangan Kombinasi Bisnis Di Laporan Keuangan PT Bank Rakyat Indonesia (Persero) Tbk - Alifia Ninda Kariza; Muhamad Fani; Riska Oktavianti; Endang Kartini Panggiarti (International Forum of Researchers and Lecturers, 2023)
Financial Accounting Standards are accounting standards compiled by official institutions. SAK contains accounting rules and procedures, one of which is the principle of presentation and disclosure (PPP). Business combination is a phenomenon of the Company to gain control over another company operating as a business. This research uses descriptive analysis to collect data relevant to the topic of discussion, conducted by reviewing the financial statements of PT Bank BRI (Persero) Tbk. which can be accessed through the Indonesia Stock Exchange website. The result of this research is that the parent company implements a business combination system by identifying the acquired party based on its acquisition value. This research aims to apply and develop the information collected to find the best solution to study the process of business combination operations in the company.